Modulating Crosscutting Concerns By The Decorator Design Pattern Vs. Aspect Oriented Programming In .NET - Pereira-Vásquez, Cristian; Vidal-Silva, Cristian; Madariaga, Erika; Jiménez, Claudia; Urzúa, Luis (My University, 2020)
This article describes and illustrates how to produce modular .NET software solutions by the use of Decorator design pattern and AspectOriented Programming (AOP) tool PostSharp. We applied both techniques for modularizing crosscutting concerns of a traditional modularization example: logging function. This work presents logging solutions with the use of Decorator and PostSharp to modularize associated cross issues, along with detailing the advantages and disadvantages of both solutions. Likewise, this work points out details of in PostSharp along with proposing the use of PostSharp and Decorator to achieve solutions with a higher level of modularity.
Keywords: AOP; .NET; Decorator; PostSharp; Crosscutting Concerns; Aspects